Upconversion luminescence of Ho3+/Tm3+/Yb3+ tri-doped NaLa(MoO4)2 phosphors. (July 2015) - Cho, Kyoungwon; Choi, Jaeha; Kim, Kang Min; Lee, Jung-Il; Ryu, Jeong Ho
Abstract: The polycrystalline Ho 3+ /Tm 3+ /Yb 3+ tri-doped NaLa(MoO4 )2 phosphors were successfully synthesized by the simple solid-state reaction method. Under the laser excitation of a 980 nm, Ho 3+ /Tm 3+ /Yb 3+ tri-doped NaLa(MoO4 )2 showed bright white upconversion (UC) emission visible to the naked eyes, which composes of blue emission at 475 nm from Tm 3+, green and red emissions at 540 nm and 651 nm from Ho 3+ . The coordinates of Ho 3+ /Tm 3+ /Yb 3+ co-doped NaLa(MoO4 )2 in the commission international de׳eclairage (CIE) chromaticity diagram could be controlled from cool to warm white color depending on Ho 3+ and Tm 3+ concentrations. The luminescent properties on Tm 3+ and Ho 3+ concentrations and UC mechanism based on laser pump power were discussed in detail.